Teaching Employability Skills Using the WonderTech Work Skills - Cairns, Kathleen V. (Canadian Journal of Counselling and Psychotherapy, 2007)
This article describes the WonderTech Work Skills Simulation, a recently developed experiential approach to leaching employability skills to adolescents and adults. The paper describes the design process of the simulation and provides a brief synopsis of its structure, content and processes.